Mannich Bases of Thiosemicarbazide: The Mutual Prodrugs as Anti-Infective Agents - Pishawikar , Sachin A.; N. More , Harinath; Kumbhar , Ravindra B.; Salokhe , Sujeet V. (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
This chapter highlights about Mannich Bases of Thiosemicarbazide. The biological activity of Mannich bases, a structurally heterogeneous class of chemical compounds that are generated from various substrates through the introduction of an aminomethyl function by means of the Mannich reaction, is surveyed, with emphasis on the relationship between structure and biological activity. The mannich base is an end product in the mannich reaction, which is nucleophilic addition reaction of a non-enolizable aldehyde and any primary or secondary amine to produce resonance stabilized imine (iminium ion or imine salt). First variety of mannich bases were synthesized using aldehyde, ketones and secondary amines having aliphatic, aromatic, cyclic and heterocyclic nature using mannich reaction. To create mannich bases of thiosemicarbazide as a mutual prodrug, the synthesized bases were condensed with thiosemicarbazide. Utilizing IR and H-NMR, produced molecules were structurally characterized. Complexity in the reactant's structure causes changes in reaction time, temperature, and end product yield percentage. Screening of compounds for anti-infectivity was performed in the form of anti- microbial activity using Escherichia Coli (8739) Staphylococcus aureus (25923), anti-fungal activity using Aspergillus niger (16404), Candida albicans (10231) using BHI (brain heart infusion) broth dilution method and anti-tubercular activity by micro plate Alamar Blue assay (MABA). Structural complexicity plays significant role in time required, temperature conditions and % yield of compounds synthesized.